Analisis Efektivitas Sistem Informasi Akuntansi Penjualan Tunai pada PT Hadji Kalla Toyota Cabang Kolaka - Sulkifli Ar; Abustan Nur; Abd. Rizal; Aiedil Pebri Suwarna; Musdalifah Musdalifah (AKUNTANSI 45, 2025)
This study aims to analyze the effectiveness of the accounting information system for cash sales at PT Hadji Kalla Toyota Kolaka Branch. The main focus of the research is on how the cash sales system for spare parts and units is implemented within the workflow involving various internal departments such as the branch head, FAH, workshop head, cashier, part admin/counter, salesman/salesgirl, story department, and treasury. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and document analysis from secondary sources. The results show that the cash sales system operates effectively and is well-integrated through the Dealer Management System (DMS), providing benefits in improving the efficiency and effectiveness of transaction processes. Additionally, the accounting information system applied by the company is based on Oracle Financials, a comprehensive accounting software that supports the financial management needs of the company optimally. There are no significant obstacles in the use of Oracle, allowing PT Hadji Kalla Toyota to maintain its operational continuity amidst intense industry competition.